1981
DOI: 10.1159/000232747
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Contact Sensitivity by Macrophages

Abstract: Lymphoid cells of mice injected with picrylsulphonic acid and then painted with picryl chloride produce a specific T suppressor factor (TSF) in vitro. This factor arms peritoneal exudate cells, which then produce a nonspecific factor which inhibits the transfer of contact sensitivity by immune cells incubated in it. An adherent, theta-negative cell, which is presumably a macrophage, is responsible. This justifies the use of the term macrophage suppressor factor. As a separate phenomenon, passive transfer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 5 publications
(7 reference statements)
0
9
1
Order By: Relevance
“…[7][8][9][10] Incubation of Mφ with TsF-containing supernatant reduced their immunogenicity as antigen-presenting cells leading to inhibition of the induction of the cellular immune response. 7 The release of secondary macrophage suppressor factor by TsF-treated Mφ was also reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10] Incubation of Mφ with TsF-containing supernatant reduced their immunogenicity as antigen-presenting cells leading to inhibition of the induction of the cellular immune response. 7 The release of secondary macrophage suppressor factor by TsF-treated Mφ was also reported.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported the ability of Mφ to bind suppressive exosomes 5 and suggested their important role in the currently investigated suppression mechanism. [6][7][8][9][10][11][12] Current studies aimed to investigate the role of Mφ in Ts cell-derived exosome-mediated suppression of the immune response as well as to determine the ability of assayed exosomes to modulate the antigen-presenting function of Mφ in the induction of humoral and cellular immunity.…”
Section: Introductionmentioning
confidence: 99%
“…In regard to the third possibility, Ptak and coworkers reported that macrophage suppressor factors are produced by antigenic stimulation* with the help of the T suppressor factor bound to the macrophage cell membrane through a Fc receptor-like molecule [32,33]. Our IgGI may play a similar role to the T suppressor factor in the production of the macro phage suppressor factor by the macrophage.…”
Section: Discussionmentioning
confidence: 97%
“…The ability of Tsup and TsF to bind antigen in the absence of MHC class II molecules is seemingly problematic given our knowledge of T‐cell receptor structure‐function and recognition of peptide–MHC molecule ligands; however, several reports have shown that T cells with a functional requirement for antigen presentation by MHC class I or II molecules have TCR that, when isolated biochemically, can show direct binding to certain antigens independent of MHC molecules, as claimed for Tsup and TsF 92–94 Infectious tolerance has been rediscovered 95,96 and is now an increasingly popular view of how Tregs work; although the mediator of this infectious process is considered to be an antigen‐unspecific cytokine, the idea that the potency of suppression is amplified by recruitment of new cells into the suppressive pool parallels the Ts1‐Ts2‐Ts3 schemes from the old Tsup days, as does the evidence that the ultimate mediation of Treg activity involves any of several immunosuppressive cytokines (transforming growth factor‐β (TGF‐β) and IL‐10 chief among these 71,73,74,97 ) that exert their activity via antigen presenting cells, just as concluded in the early Tsup studies 98 …”
Section: Are Tregs Really Tsup In Disguise?mentioning
confidence: 90%
“…Infectious tolerance has been rediscovered 95,96 and is now an increasingly popular view of how Tregs work; although the mediator of this infectious process is considered to be an antigen-unspecific cytokine, the idea that the potency of suppression is amplified by recruitment of new cells into the suppressive pool parallels the Ts1-Ts2-Ts3 schemes from the old Tsup days, as does the evidence that the ultimate mediation of Treg activity involves any of several immunosuppressive cytokines (transforming growth factor-b (TGF-b) and IL-10 chief among these 71,73,74,97 ) that exert their activity via antigen presenting cells, just as concluded in the early Tsup studies. 98 Finally, what lessons should be drawn from the rise and fall of Tsup and the recent impact of Treg studies? At a minimum, given the list above, it seems that the field threw the baby out with the bathwater.…”
Section: Are Tregs Really Tsup In Disguise?mentioning
confidence: 99%